Review of literature on capital structure: Independent and Dependent Variables - Chaudhary, Bharti; Singh, Netra Pal; Mittal, Ruby (Universitas Airlangga, 2024)
Choosing a capital structure presents many difficulties for businesses. Choosing the right balance between debt and equity is one of the most important decisions. A poor capital structure decision has the power to completely ruin any company's success. Researchers have shown interest in analyzing the capital structure of the companies. The main objective of this paper to review these empirical studies of capital structure and to identify frequently used parameter by the researchers for last 14 years. The empirical capital structure literature is reviewed in this paper, with a focus on works released since 2010. The research paper also intends to address particular issues for further investigation while highlighting the significant gaps in the literature on the factors influencing capital structure and it compares the outcomes of practical research with theoretical expectations. This study investigates the independent factors and their dependent effects that lead companies to stray from ideal capital structures. This study primarily focuses on review of studies in the context of: (i) Capital structure in the banking and financial institutions sector; (ii) Capital structure in the metals industry; (iii) Retail industry; (iv) Software industry; and (v) Pharmaceutical industry. Only secondary data were used in this present study.